Объяснение:
а)
[tex]\displaystyle\\y=e^x*lnx\\\\y'=(e^x*lnx)'=(e^x)'*lnx+e^x*(lnx)'=e^x*lnx+\frac{e^x}{x} .\\\\y'=(e^x*lnx+\frac{e^x}{x})'=(e^x*lnx)'+(\frac{e^x}{x} )'=e^x*lnx+\frac{e^x}{x} +\frac{(e^x)'*x-e^x*x'}{x^2} =\\\\=e^x*lnx+\frac{e^x}{x} +\frac{e^x}{x} -\frac{e^x}{x^2} =e^x*lnx+\frac{2e^x}{x} -\frac{e^x}{x^2}.[/tex]
b)
[tex]y=5x^5+3x^3\\\\y'=(5x^5+3x^3)'=5*5*x^4+3*3*x^2=25x^4+9x^2.\\\\y'=(25x^4+9x^2)'=25*4*x^3+9*2*x=100x^3+18x.[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
а)
[tex]\displaystyle\\y=e^x*lnx\\\\y'=(e^x*lnx)'=(e^x)'*lnx+e^x*(lnx)'=e^x*lnx+\frac{e^x}{x} .\\\\y'=(e^x*lnx+\frac{e^x}{x})'=(e^x*lnx)'+(\frac{e^x}{x} )'=e^x*lnx+\frac{e^x}{x} +\frac{(e^x)'*x-e^x*x'}{x^2} =\\\\=e^x*lnx+\frac{e^x}{x} +\frac{e^x}{x} -\frac{e^x}{x^2} =e^x*lnx+\frac{2e^x}{x} -\frac{e^x}{x^2}.[/tex]
b)
[tex]y=5x^5+3x^3\\\\y'=(5x^5+3x^3)'=5*5*x^4+3*3*x^2=25x^4+9x^2.\\\\y'=(25x^4+9x^2)'=25*4*x^3+9*2*x=100x^3+18x.[/tex]